The perceptions of bankers and regulators on Islamic microfinance: A case study of Pakistan - Abbas, Kausar; Abdul Razak, Dzuljastri (2013)
This research study deals with the perceptions of bankers and regulators on the issues and challenges concerning the implementation of Islamic microfinance in Pakistan; and the adoption of an appropriate instrument to Islamic microfinance for poverty alleviation as an alternative to the conventional model of microfinance. The study adopted the methodology of questionnaire survey. Five full-fledged Islamic banks of Pakistan were used in the study. A total of 100 people were surveyed by means of self- administered questionnaire and the response rate was 50 %. Three of the sample banks were selected from Islamabad and two banks from Lahore because of the well-established banks in these two cities of Pakistan. The findings are divided into four sections: Function of Islamic microfinance in poverty alleviation, Islamic microfinance’s contribution to community, Islamic bank’s approach towards Islamic microfinance and Challenges for Islamic microfinance. In general, the Islamic bankers agreed that Islamic banks should offer Islamic microfinance and treat it separately from other products. Generally, both top and middle management agreed that Murabahah, Dimishing musharakah and Ijarah are most applicable models for Islamic microfinance schemes to the potential micro-entrepreneurs. Therefore, the findings could provide insights to Islamic banks in diversifying their products by offering Islamic microfinance to the poor but with proper guidelines and policies.